2005
DOI: 10.1086/498570
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Type Ib Supernova 2005bf: A WN Star Explosion Model for Peculiar Light Curves and Spectra

Abstract: Observations and modeling for the light curve (LC) and spectra of supernova (SN) 2005bf are reported. This SN showed unique features: the LC had two maxima, and declined rapidly after the second maximum, while the spectra showed strengthening He lines whose velocity increased with time. The double-peaked LC can be reproduced by a double-peaked 56 Ni distribution, with most 56 Ni at low velocity and a small amount at high velocity. The rapid post-maximum decline requires a large fraction of the γ-rays to escape… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
87
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 28 publications
(31 reference statements)
14
87
0
Order By: Relevance
“…However, as shown in Figure 4, the He I velocities in SNe 2005bf and 2011dh increase with time, if the He I λ5876 velocities at the earliest phase are ignored. As explained in Tominaga et al (2005), the increasing He I velocities may be the result of increasing nonthermal excitation. Folatelli et al (2014) introduced a family of flat-velocity SNe IIb (SNe fvIIb) whose velocities stay roughly the samebetween 6000 and 8000 km s −1 -during the photospheric phase.…”
Section: Absorption Velocities Of He I Lines In Sne Iib and Sne Ibmentioning
confidence: 87%
See 1 more Smart Citation
“…However, as shown in Figure 4, the He I velocities in SNe 2005bf and 2011dh increase with time, if the He I λ5876 velocities at the earliest phase are ignored. As explained in Tominaga et al (2005), the increasing He I velocities may be the result of increasing nonthermal excitation. Folatelli et al (2014) introduced a family of flat-velocity SNe IIb (SNe fvIIb) whose velocities stay roughly the samebetween 6000 and 8000 km s −1 -during the photospheric phase.…”
Section: Absorption Velocities Of He I Lines In Sne Iib and Sne Ibmentioning
confidence: 87%
“…Since the progenitor stars may have different amounts of hydrogen present before explosion (since the various mechanisms may not have removed all of the hydrogen), we may expect different amounts, including small amounts, of hydrogen still present at the time of explosion. However, it is not easy to identify Hα because the absorption feature at the expected position of Hα-the "6300 Åabsorption line"-can be due to C II λ6580, Ne I λ6402, or Si II λ6355 as well (e.g., Branch et al 2002;Tominaga et al 2005;Elmhamdi et al 2006;Parrent et al 2007).…”
Section: Is There Hα In the Spectra Of Sne Ib?mentioning
confidence: 99%
“…Several other supernovae have been observed and studied in detail since then. Some of the most interesting studies have been those of the type Ib SN 2005bf which showed the presence of a thin hydrogen envelope (Anupama et al, 2005b;Tominaga et al, 2005), the underluminous, peculiar type Ia SN 2005hk , the highly reddened type Ia SN 2003hx (Misra et al, 2008), the type Ibn SN 2006jc -a type Ib supernova with narrow He emission lines (Anupama et al, 2009), the broad line type Ic SN 2007ru that showed a high kinetic energy to ejected mass ratio ), the extremely slow type Ib SN 2009jf that showed signs of asphericity (Sahu et al, 2011) and the transitional type Ia event SN 2009an (Sahu et al, 2013). Figure 9 shows one of the recent supernovae in the nearby galaxy M82 obtained with TIRSPEC.…”
Section: Stellar Explosionsmentioning
confidence: 99%
“…SN 2005bf was a peculiar Type Ib/c SN. It showed a double‐peaked light curve with a first maximum at ∼16 d post‐explosion and a second, brighter maximum at ∼40 d post‐explosion (Folatelli et al 2006), assuming an explosion date of 2005 March 28 (Tominaga et al 2005). At early epochs little or no He was observed, giving some resemblance to a Type Ic SN (Modjaz et al 2005; Morrell et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At early epochs little or no He was observed, giving some resemblance to a Type Ic SN (Modjaz et al 2005; Morrell et al 2005). By the second maximum, He i was observed in the spectrum (Wang & Baade 2005), giving the appearance of a Type Ib SN (Tominaga et al 2005; Folatelli et al 2006). Tominaga et al (2005) and Folatelli et al (2006) invoke ‘jets’ and ‘holes’ to explain the observed behaviour.…”
Section: Introductionmentioning
confidence: 99%